Ethical Principles of Autonomy for Hypertension Patients : A concept analysis. - Endang Triyanto; Sidik Awaludin; Zuhariah Felis (ACHSM, 2024)
Background: Autonomy is a fundamental ethical principle within the nursing profession. It plays a significant role in patients' decision-making processes when seeking nursing interventions. In the context of hypertensive individuals, autonomy pertains to their capacity to manage and regulate their hypertensive condition. This encompasses the independent decision-making related to medications, lifestyle adjustments, and overall care. Method: The method utilized for this analysis is the Walker & Avant approach (2011). The concept analysis was conducted by consulting literature on autonomy sourced from Google Scholar and Preplexity databases. The search keywords employed were "concept of autonomy" and "hypertension sufferers". Results: The concept analysis followed the 8-step method outlined by Walker and Avant. This systematic approach, which involves identifying the attributes, antecedents, and consequences of autonomy, leads to the development of an operational definition. Autonomy is defined as the capacity of an individual to make decisions independently, without external influence, to manage themselves and take responsibility for the outcomes of those decisions. Conclusion: the results of the analysis it was found that autonomy is very beneficial for hypertension sufferers because a person can make decisions, so that they have self-satisfaction, increased motivation and clear life goals. Autonomy grants nurses the freedom to make clinical decisions based on their professional knowledge and skills. Nurses can determine the best course of action for patients without having to wait for instructions from a doctor, while still being accountable for their decisions and ready to explain their actions within the context of ethics and law.